2020
DOI: 10.1007/s10643-020-01063-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Knowledge and Needs of Early Childhood Development Practitioners from a Low-Resource Community

Abstract: Early childhood development (ECD) practitioners from low-resource communities may find it challenging to provide developmentally appropriate services to support child development, due to the increased risk of developmental delays. Practitioners rely on their ECD knowledge when delivering ECD services, but many practitioners in South Africa are underqualified. The knowledge and needs of practitioners from low-resource communities should be explored to develop and implement appropriate support services. A combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…This result showed that awareness of parents with higher education degrees concerning the “first thousand days and the effect this period on children’s development” is higher than the awareness of other parents. This result is consistent with the findings of previous studies that showed the awareness of educated parents, especially mothers [ 30 ], and knowledge of professionals [ 36 ] with higher education about early childhood development are higher. On the contrary, this study showed that the education degree has an inverse relationship with the awareness concerning the “use of digital media by children”.…”
Section: Discussionsupporting
confidence: 93%
“…This result showed that awareness of parents with higher education degrees concerning the “first thousand days and the effect this period on children’s development” is higher than the awareness of other parents. This result is consistent with the findings of previous studies that showed the awareness of educated parents, especially mothers [ 30 ], and knowledge of professionals [ 36 ] with higher education about early childhood development are higher. On the contrary, this study showed that the education degree has an inverse relationship with the awareness concerning the “use of digital media by children”.…”
Section: Discussionsupporting
confidence: 93%
“…Improved knowledge scores confirm that the mHealth training program provided meaningful educational information and that the training successfully met learning objectives on hearing health in young children ( Table 1 ). ECD practitioners’ knowledge is crucial for inclusive ECD classes, where exceptional teaching and caring practices are necessary for the holistic development of vulnerable children [ 14 , 38 ]. With the widespread diversity and background of children in ECD centres and schools, especially in LMICs, teachers and ECD practitioners need specialised knowledge competencies and skills to provide nurturing care and an auspicious learning environment for children with special needs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early childhood development (ECD) programs aim to provide services for optimal childhood development while ensuring general health. ECD centres, particularly in LMICs and low-socioeconomic-status (SES) communities, serve as front-line healthcare platforms for early detection, with ECD practitioners often acting as primary caregivers [ 14 , 15 ]. Therefore, ECD practitioners play a critical role in preventing and detecting developmental risks in young children, including hearing loss [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers must constantly deal with a lack of resources, poor infrastructure at centres and children who grew up in deprived circumstances (Baloyi and Makhubela, 2018). Additionally, poor management of government services exacerbates the problems related to early childhood education (Smit et al , 2021; Visser et al , 2021). The factors mentioned above necessitate research regarding the well-being of early childhood teachers (Cumming, 2017; Hall-Kenyon et al , 2014).…”
Section: Methodsmentioning
confidence: 99%